Spatial Cognition VI. Learning, Reasoning, and Talking about Space - Freks, Christian (Springer, 2017)
This book constitutes the refereed proceedings of the International Conference on Spatial Cognition, Spatial Cognition 2008, held in Freiburg, Germany, in September 2008. The 27 revised full papers presented together with 3 invited lectures were carefully reviewed and selected from 54 submissions. The papers are organized in topical sections on spatial orientation, spatial navigation, spatial learning, maps and modalities, spatial communication, spatial language, similarity and abstraction, concepts and reference frames, as well as spatial modeling and spatial reasoning.